2011
DOI: 10.1016/j.ajog.2011.06.026
|View full text |Cite
|
Sign up to set email alerts
|

National Diabetes Data Group vs Carpenter-Coustan criteria to diagnose gestational diabetes

Abstract: Objective To compare perinatal outcomes among women diagnosed with gestational diabetes by National Diabetes Data Group (NDDG) with women only meeting Carpenter-Coustan criteria. Study design Fourteen-year retrospective cohort; women screened positive with 1-hour glucose load ≥140 mg/dL underwent a diagnostic 3-hour oral glucose tolerance test. We report adjusted prevalence ratios (aPR) of multivariate analyses. Results Of the 4659 screen-positive women with diagnostic testing, 1082 (3.3%, 1082/33,179) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
7
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 22 publications
5
44
7
3
Order By: Relevance
“…The results also showed that CC criteria would identify 27.6% more GDM cases during their first visit, at an average of 13 weeks earlier than using NDDG criteria. These findings are similar to those of previous studies, which found an increase in GDM prevalence of between 30% and 50% [7,12]. These findings can be explained by the increased sensitivity of CC criteria because of lower thresholds compared with NDDG criteria.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The results also showed that CC criteria would identify 27.6% more GDM cases during their first visit, at an average of 13 weeks earlier than using NDDG criteria. These findings are similar to those of previous studies, which found an increase in GDM prevalence of between 30% and 50% [7,12]. These findings can be explained by the increased sensitivity of CC criteria because of lower thresholds compared with NDDG criteria.…”
Section: Discussionsupporting
confidence: 82%
“…Whether women with OGTT values above the CC threshold, but below the NDDG threshold, are at increased risk of adverse perinatal outcomes has been inconsistently reported [8,9,11,12,14,15]. The results of this study revealed that, while mean birth weight was comparable between CC only and NDDG groups, it was significantly greater than in those without GDM (P <0.001).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…16,17 In the present study, however, the incidence of LGA was no statistically difference among the three groups. As a result, the incidence of maternal complications between group 1 and 2 was not different.…”
Section: Discussioncontrasting
confidence: 77%